PEMODELAN JUMLAH KEMATIAN BAYI DI PROVINSI MALUKU TAHUN 2010 DENGAN MENGGUNAKAN REGRESI POISSON - Aulele, Salmon N. (PATTIMURA UNIVERSITY, 2012)
Infant mortality is an experienced child death before the age of one year. Regression analysis is a statistical analysis that aims to model the relationship between responsevariables (Y) with predictor variables (X). If the Poisson distributed response variables (Y), the regression model used was Poisson regression. The purpose of this research is to get aPoisson regression model according to the significant factors that influence the infant mortality. The results shows that the significant factors are influence the infant mortality asthe presentation of non medical childbirth (X1) and quantity of medical facility (X7). The case studies are infant mortality in Provinsi Maluku in 2010.